Rectal cancer: neoadjuvant chemoradiotherapy - Rödel, Claus; Hofheinz, Ralf-Dieter; Fokas, Emmanouil (Best practice & research. Clinical gastroenterology, 2016)
The monolithic approach to apply the same schedule of preoperative 5-fluorouracil (5-FU)- or capecitabine-based chemoradiotherapy (CRT) to all patients with clinically staged TNM stage II/III rectal cancer need to be questioned. Five randomized trials have been completed to determine if the addition of oxaliplatin to preoperative 5-FU/capecitabine-based CRT offers an advantage compared with single-agent CRT. In contrast to the German CAO/ARO/AIO-04 trial, results from the ACCORD 12, STAR-01, PETACC-6 and NSAPB R-04 trials failed to demonstrate a significant improvement of early or late efficacy endpoints with the addition of oxaliplatin. Most of the phase II trials incorporating cetuximab into CRT reported disappointingly low rates of pCR; the combination of CRT with VEGF inhibition showed encouraging pCR rates but at the cost of increased surgical complications. Novel clinical trials currently address (1) the role of induction and consolidation chemotherapy before or after CRT, (2) minimal or omitted surgery following complete response to CRT, or (3) the omission of radiotherapy for selected patients with response to neoadjuvant chemotherapy. The notion of different multimodal treatment concepts according to tumor stage, location, mesorectal fascia margin status, molecular profiles, tumor response, and patients' preferences becomes increasingly popular and will render the multimodal treatment approach of rectal cancer more risk-adapted.
Gesehen am 19.09.2019